"Arabic is Not my Language…": Debates over Teaching of Arabic in Irish Muslim Schools. Issue 4 (2nd October 2017) - Sai, Youcef
Abstract: Based on ethnographic fieldwork that took place in 2014 in two Irish primary Muslim schools in the Republic of Ireland, this article draws from both observations of Arabic classes from fourth and fifth classes as well as semi-structured interviews with teachers and parents. The research findings explore the content of and approaches towards the teaching of Arabic and the views held by participants towards the learning of Arabic as part of Islamic religious education. The study reveals the diversity of views that exist and questions the importance of learning Arabic, as part of formal religious education for young Muslims living in non-Muslim pluralist societies. The author concludes with some implications from the study and offers some direction for Muslim schools as it relates to teaching Arabic and, more broadly, to Islamic religious education of young Muslims in Western contexts.